The expression of Lamin A mutant R321X leads to endoplasmic reticulum stress with aberrant Ca2+ handling. Issue 11 (15th July 2016) - Carmosino, Monica; Gerbino, Andrea; Schena, Giorgia; Procino, Giuseppe; Miglionico, Rocchina; Forleo, Cinzia; Favale, Stefano; Svelto, Maria
Abstract: Mutations in the Lamin A/C gene ( LMNA ), which encodes A‐type nuclear Lamins, represent the most frequent genetic cause of dilated cardiomyopathy (DCM). This study is focused on a LMNA nonsense mutation (R321X) identified in several members of an Italian family that produces a truncated protein isoform, which co‐segregates with a severe form of cardiomyopathy with poor prognosis. However, no molecular mechanisms other than nonsense mediated decay of the messenger and possible haploinsufficiency were proposed to explain DCM. Aim of this study was to gain more insights into the disease‐causing mechanisms induced by the expression of R321X at cellular level. We detected the expression of R321X by Western blotting from whole lysate of a mutation carrier heart biopsy. When expressed in HEK293 cells, GFP‐ (or mCherry)‐tagged R321X mislocalized in the endoplasmic reticulum (ER) inducing the PERK‐CHOP axis of the ER stress response. Of note, confocal microscopy showed phosphorylation of PERK in sections of the mutation carrier heart biopsy. ER mislocalization of mCherry‐R321X also induced impaired ER Ca 2+ handling, reduced capacitative Ca 2+ entry at the plasma membrane and abnormal nuclear Ca 2+ dynamics. In addition, expression of R321X by itself increased the apoptosis rate. In conclusion, R321X is the first LMNA mutant identified to date, which mislocalizes into the ER affecting cellular homeostasis mechanisms not strictly related to nuclear functions.